PENGEMBANGAN MEDIA WAYANG SUKET PENGEMBANGAN MEDIA WAYANG SUKET UNTUK MENINGKATKAN KEPEDULIAN LINGKUNGAN DI KELAS IV MI AL-HUDA PLOSO PACITAN : DEVELOPMENT OF SUKET WAYANG MEDIA TO IMPROVE ENVIRONMENTAL CONCERN IN GRADE IV OF MI AL-HUDA PLOSO PACITAN - Biqi Zain; Rimba Maulana; Aziz Assa’diy (STKIP Subang, 2025)
This study aims to determine the effect of wayang suket media on the level of environmental awareness among fourth-grade students at MI Al-Huda Ploso Pacitan. Sampling was conducted using a questionnaire given to 10 fourth-grade students. The subjects of this study were 10 fourth-grade students. The results showed that the students' level of environmental awareness increased significantly, as evidenced by the results of expert validation of the material, which scored 93.75% across all aspects, meeting the “Valid” criterion, and expert validation of the media, which scored 91% across all aspects, also meeting the “Valid” criterion. The measurement of the suitability of the suket puppet media by teachers obtained a score of 100% for all aspects with a criterion of “Very Suitable”. Student responses to the attractiveness of the product showed maximum results with an average of 98.7% for all aspects with a criterion of “Very Attractive”. It can be concluded that the suket puppet media for teaching norms in life is very attractive to be applied in learning. The level of student awareness after the implementation of the suket puppet media material on norms in life showed an increase in each student with an average of 90%, which falls under the “High Increase” criterion.